"I can't carry on like this": a feminist perspective on the process of exiting sex work in a South African context - Hakala, Suvi; Keller, Marike (Department of Psychology, 2014)
This study aims to look at the challenges faced by women of low socio-economic status in exiting sex work, in a South African context where gender-based violence is normalized and widespread. In doing so, this research applies principles of feminist theory to create a contextualized understanding of the process of exit. Two focus groups, with a total of 18 non-transgendered women were conducted in an informal setting, resulting in an open-ended discussion around these challenges. These interviews were recorded, transcribed and analyzed using thematic analysis. The categories and themes emerging from this analysis were past trauma, motherhood, partnerships, social support, economic necessity, employment and gossip. These themes are permeated by a pattern of escapism. This pattern exemplifies their disempowerment and lack of agency, which is symptomatic of the gender oppression pervading their lives. The results of this research will be used to draw up a policy in collaboration with the NGO Embrace Dignity, for parliament, to initiate legal reform relating to sex work.